"Two-Dimensional Nanosheets Produced by Liquid Exfoliation of Layered Materials" - COLEMAN, JONATHAN; DONEGAN, JOHN; BOLAND, JOHN; KIM, HYE; NICOLOSI, VALERIA; SHVETS, IGOR; DUESBERG, GEORG (My University, 2011)
If they could be easily exfoliated, layered materials would become a diverse source of 2-dimensional crystals whose properties would be useful in applications from electronics to energy storage. We show that layered compounds such as MoS2, WS2, MoSe2, MoTe2, TaSe2, NbSe2, NiTe2, BN and Bi2Te3, can be efficiently dispersed in common solvents and can be deposited as individual flakes or formed into films. Electron microscopy confirms the material to be exfoliated into individual layers. By blending with suspensions of other nano-materials or polymer solutions, we can prepare hybrid dispersions or composites which can be cast into films. We show that WS2 and MoS2 effectively reinforce polymers, while WS2/carbon nanotube hybrid films have high conductivity leading to promising thermoelectric properties.
PUBLISHED
Keywords: exfoliate layered compounds; exfoliate layered compounds